Whether Probiotic Supplementation Benefits Rheumatoid Arthritis Patients: A Systematic Review and Meta-Analysis. (February 2017) - Pan, Hudan; Li, Runze; Li, Ting; Wang, Jun; Liu, Liang
Abstract: Gut and oral microflora are important factors in the pathogenesis and development of rheumatoid arthritis (RA). Recent studies have shown that probiotic supplements have beneficial consequences on experimental arthritis in rats. However, results from randomized clinical trials on the effects of probiotics have not been consistent. The aim of this study was to systematically review the existing evidence for the effects of probiotic intervention in RA. We included randomized controlled trials (RCTs) of RA patients receiving stable treatment with disease-modifying anti-rheumatic drugs (DMARDs) that: ① were combined with additional probiotic supplements or ② were combined with either no additional supplements or only a placebo treatment. Statistical analysis was performed using Review Manager 5.3.3. Six randomized clinical trials were eligible for inclusion in the meta-analysis, with 249 participants in total. The results showed that the probiotic intervention treatment has not yet achieved significant improvement in the American College of Rheumatology 20% improvement criteria (ACR20) score and the disease activity score in 28 joints (DAS28). The laboratory index C-reactive protein (CRP) (mg·L −1 ) was significantly reduced in the intervention group. The expression of inflammatory cytokines tumor necrosis factor (TNF)-α and interleukine (IL)−1β was also significantly reduced, while IL-10 expression increased in the probiotic intervention groups. This article is the first systematic review and meta-analysis providing a comprehensive assessment of the benefits of treating RA with probiotics. We found that probiotic supplementation may show a limited improvement in RA therapy in existing reports because of a lack of sufficiently high-quality work on the part of clinicians. More multi-centered, large-sample RCTs are needed in order to evaluate the benefits of probiotics in RA treatment.